Carbonic anhydrase IX downregulation linked to disruption of HIF-1, NFκB and STAT3 pathways as a new mechanism of ibuprofen anti-cancer effect - Katarina Grossmannova; Petra Belvoncikova; Barbora Puzderova; Veronika Simko; Lucia Csaderova; Jaromir Pastorek; Monika Barathova (PLoS ONE, 2025)
Numerous studies have highlighted the anti-cancer effects of nonsteroidal anti-inflammatory drugs (NSAIDs), although the underlying mechanisms remain unclear. This study focuses on elucidating the impact of the NSAID ibuprofen (IBU) on cancer cells exposed to hypoxia, as the hypoxic microenvironment significantly influences tumor progression, metastatic potential, and therapy resistance. Given that carbonic anhydrase IX (CA IX) is a key hypoxia-associated protein and a promising therapeutic target due to its tumor-specific expression, we primarily examined the impact of IBU on CA IX and the transcription factors regulating CA IX expression. We found that IBU downregulates expression and protein level of CA IX in hypoxic colon carcinoma and head and neck cancer cells, resulting in a reduction of membranous CA IX. To elucidate the mechanism of this phenomenon, we analyzed the key CA IX-regulating transcription factor HIF-1 and found decreased levels of the HIF-1α subunit in IBU-treated cells, leading to its impaired binding to the CA9 promotor. Analysis of another transcription factor involved in CA IX expression, NFκB, showed suppressed NFκB pathway under IBU treatment. Moreover, we demonstrated IBU-mediated induction in apoptosis in cancer cells, as well as a decrease in their ability to migrate. Our study is the first to demonstrate that ibuprofen downregulates carbonic anhydrase IX expression in hypoxic colon and head and neck tumor cells by decreasing HIF-1α levels. Additionally, ibuprofen impairs key transcription factors NFκB and STAT3, leading to reduced adaptation to hypoxic stress, decreased tumor cell viability, and migration. This indicates its potential as a therapeutic agent in combination therapy for colon carcinoma or head and neck cancer.